Strategy Analysis of Islamic Banking Study Program Students to Become Banking Employees - Pramita, Yuni; Sunarto, Andang; Sumarni, Yenti; Homa Hoodfar (Yayasan Darussalam Bengkulu, 2024)
The aim of this research is to determine the strategy for Sharia Banking Study Program Students to become Banking Employees. This research is field research, using a descriptive qualitative approach. The data sources used in this research are primary data and secondary data. The data analysis technique used is data reduction, data presentation and drawing conclusions. This research data collection used observation, interview and documentation techniques. The research results show that students have significant opportunities, such as Islamic religious background, knowledge of sharia banking products, product marketing skills, and the application of morals in everyday interactions. On the other hand, threats to students include banks' lack of priority towards graduates with a sharia banking educational background, recruitment policies that prioritize physical appearance, and limited information about available recruitment. To overcome this challenge, students can apply strategies such as utilizing experience and knowledge from lectures and field work practices, increasing understanding of sharia banking principles through organizational activities to train public speaking, seminars, partnership program training from sharia banks for students, and being active in seeking recruitment through social media. Thus, opportunities, anticipating threats, and implementing the right strategies can help students increase their chances of becoming sharia bank employees.